Explaining regional differences in self-employment rates in Spain. - Bego\~na Cueto (European Regional Science Association (ERSA), 2010)
There are interesting differences in self-employment rates among countries and also among regions within the same country. There is a multiplicity of reasons to explain the evolution of self-employment and the differences among countries and/or regions. However, unemployment and the distribution of employment (by sex, age, level of education and by sector) are the usual explanatory factors. Spain has one of the highest self-employment rates in the context of Europe (over 20%). During the period 1986-2005 it increased by almost a million people. We notice that the growth was higher in 1993-2005 than in 1986-1992, corresponding to the evolution of the Spanish economy with the highest period of job creation from 1995 onwards. There are interesting regional differences among the autonomous communities. In 1986 the self-employment rate ranged from 14.5% to 24.5%. This variety was maintained during the analysed period and the majority of the regions also kept their position. The aim of this paper is to explain the regional differences in the self-employment rates of the Spanish autonomous communities. We have data for the seventeen Spanish autonomous communities from 1986 to 2008. The dependent variable in the models is the self-employment rate. In order to estimate the determinants of differences in regional self-employment rates we include in our model variables that reflect the labour market conditions and also institutional factors. The previous literature on self-employment suggests several potential explanatory variables: unemployment rate, proportion of long-term unemployed, demographic and industrial composition of the labour force Preliminary results show the relevance of the educational level of the workforce as well as the significance of the labour market situation (good conditions of the labour market -a high employment rate or a small proportion of fixed-term contracts- contribute to reduce the self-employment ratio).
Keywords: J23; 330; self-employment; regional differences; panel data